Supervision of community health workers in Mozambique: a qualitative study of factors influencing motivation and programme implementation - Ndima, Sozinho Daniel (Hum Resour Health, 2015)
BACKGROUND: Community health workers (CHWs) in Mozambique (known as Agentes Polivalentes Elementares (APEs)) are key actors in providing health services in rural communities. Supervision of CHWs has been shown to improve their work, although details of how it is implemented are scarce. In Mozambique, APE supervision structures and scope of work are clearly outlined in policy and rely on supervisors at the health facility of reference. The aim of this study was to understand how and which aspects of supervision impact on APE motivation and programme implementation. METHODS: Qualitative research methodologies were used. Twenty-nine in-depth interviews were conducted to capture experiences and perceptions of purposefully selected participants. These included APEs, health facility supervisors, district APE supervisors and community leaders. Interviews were recorded, translated and transcribed, prior to the development of a thematic framework. RESULTS: Supervision was structured as dictated by policy but in practice was irregular and infrequent, which participants identified as affecting APE’s motivation. When it did occur, supervision was felt to focus more on fault-finding than being supportive in nature and did not address all areas of APE’s work – factors that APEs identified as demotivating. Supervisors, in turn, felt unsupported and felt this negatively impacted performance. They had a high workload in health facilities, where they had multiple roles, including provision of health services, taking care of administrative issues and supervising APEs in communities. A lack of resources for supervision activities was identified, and supervisors felt caught up in administrative issues around APE allowances that they were unable to solve. Many supervisors were not trained in providing supportive supervision. Community governance and accountability mechanisms were only partially able to fill the gaps left by the supervision provided by the health system. CONCLUSION: The findings indicate the need for an improved supervision system to enhance support and motivation and ultimately performance of APEs. Our study found disconnections between the APE programme policy and its implementation, with gaps in skills, training and support of supervisors leading to sub-optimal supervision. Improved methods of supervision could be implemented including those that maximize the opportunities during face-to-face meetings and through community-monitoring mechanisms.